Association between Food Deserts and Gestational Diabetes Mellitus in a Large Metropolitan Area - Banner, Grace C.; Weaver, Kingsley N.; Rushovich, Tamara; York, Sloane L.; Yee, Lynn M. (American Journal of Perinatology, 2020)
Objective The aim of this study is to determine the relationship between urban food deserts and frequency and obstetric outcomes related to gestational diabetes.Study Design We conducted a retrospective cohort study of singleton births in Chicago from 2010 to 2014. Birth certificate data were analyzed and geomapped by census tract. Census tracts were categorized as “food deserts” according to the USDA Food Access Research Atlas. The primary outcome was frequency of gestational diabetes. Secondary outcomes were assessed among women with gestational diabetes and their neonates.Results Of the 191,947 eligible women, 8,709 (4.5%) were diagnosed with gestational diabetes. Those in food deserts were more likely to be younger, obese, minority race/ethnicity, and multiparous. Women in food deserts were less likely to develop gestational diabetes (3.8 vs. 4.8%, p < 0.01; adjusted odds ratio 0.91, 95% confidence interval 0.86–0.96). Women with gestational diabetes did not experience worse maternal and neonatal outcomes after controlling for potential confounders.Conclusion In contrast to prior work, women in Chicago living within food deserts were less likely to develop gestational diabetes and did not experience poorer outcomes, suggesting environmental factors other than food access contribute to perinatal outcomes.
Keywords: food desert; gestational diabetes mellitus; health outcomes; food access